2021
DOI: 10.1002/cpp.2678
|View full text |Cite
|
Sign up to set email alerts
|

Individual psychotherapy can reduce suicidal ideation in first episode psychosis: Further findings from the 2‐year follow‐up of the ‘Parma Early Psychosis’ programme

Abstract: Introduction: Suicidal thinking is relevant in patients with First Episode Psychosis (FEP). However, longitudinal studies specifically examining treatment response for suicidal ideation in FEP are still relatively scarce, especially with long-term design and in real-world clinical settings. The aims of this research were (A) to longitudinally assess suicidal thoughts in people with FEP along a 2-year follow-up period and (B) to overtime investigate any significant association of suicidal ideation levels with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As previous studies have reported, years of education (Zhang et al, 2018), DUP, and tobacco and alcohol consumption (Ayesa‐Arriola et al, 2015, 2018; Lopez‐Morinigo et al, 2019; Pelizza et al, 2020; Pelizza et al, 2021) were not related to suicidal behaviour.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…As previous studies have reported, years of education (Zhang et al, 2018), DUP, and tobacco and alcohol consumption (Ayesa‐Arriola et al, 2015, 2018; Lopez‐Morinigo et al, 2019; Pelizza et al, 2020; Pelizza et al, 2021) were not related to suicidal behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…Compared to healthy controls, patients presented more suicidal ideation, suicide attempts, more suicide risk and higher overall scores in the total Plutchik Suicide Risk Scale; which, overall, is congruent with previous research (Dutta et al, 2010; Falcone et al, 2010; Zhang et al, 2018). These results highlight the importance of implementing suicide prevention interventions in people with first episode psychosis (Pelizza et al, 2021).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations